On Japanese Gardens Located far away from Japan with Comparisons and Random Coincidences - Olga Smirnova (Проект Байкал, 2017)
The article observes peculiarities of Japanese gardens located in Great Britain and the USA. Their symbolics, traditions and techniques used for their creation are described. The article features several elements of the gardens and how they depend on the national mentality of the country of their location. According to the article, at present time, there is no deep understanding of the specifics of Japanese garden culture in Great Britain and the USA, and the images of China and Japan contaminate.